Case Report: Primary Hypothyroidism Associated With Lutetium 177-DOTATATE Therapy for Metastatic Paraganglioma - Gubbi, Sriram; Al-Jundi, Mohammad; Del Rivero, Jaydira; Jha, Abhishek; Knue, Marianne; Zou, Joy; Turkbey, Baris; Carrasquillo, Jorge Amilcar; Lin, Emily; Pacak, Karel; Klubo-Gwiezdzinska, Joanna; Lin, Frank I-Kai (Frontiers in Endocrinology, 2021)
Background Lutetium 177 (177Lu) - DOTATATE is a form of peptide receptor radionuclide therapy (PRRT) utilized in the treatment of neuroendocrine tumors. Data on 177Lu-DOTATATE-induced thyroid dysfunction is limited. Case Description A 29-year-old male with SDHB positive metastatic paraganglioma enrolled under the 177Lu-DOTATATE trial (NCT03206060) underwent thyroid function test (TFT) evaluation comprised of thyroid stimulating hormone (TSH) and free thyroxine (FT4) immunoassay measurements per protocol prior to 177Lu-DOTATATE therapy. The TSH was suppressed [<0.01 µIU/ml (0.27–4.2 µIU/ml)], and FT4 was normal [1.3 ng/dl (0.9–1.7 ng/dl)]. The TSH receptor antibody and thyroid stimulating immunoglobulin index were undetectable [<1 IU/L (≤1.75 IU/L), and <1 (≤1.3) respectively], while the anti-thyroid peroxidase (anti-TPO) and anti-thyroglobulin (anti-Tg) antibodies were elevated [605 IU/ml (0.0–34.9 IU/ml), and 178 IU/ml (0.0-40.0 IU/ml) respectively]. Mass spectrometry on a stored (-80°C) plasma sample obtained one-month pre-PRRT revealed elevated total triiodothyronine (TT3) [235 ng/dl (65–193 ng/dl)] and FT4 [3.9 ng/dl (1.2–2.9 ng/dl)] levels. The patient was diagnosed with Hashimoto’s thyrotoxicosis. However, the patient was asymptomatic. One month after the first dose of 200mCi 177Lu-DOTATATE, the patient noted fatigue and a 2.6 Kg weight gain. The TSH (73.04 µIU/ml), anti-TPO antibodies (>1,000 IU/ml), and anti-Tg antibodies (668 IU/ml) had substantially increased, with reductions in FT4 (0.3 ng/dl) and TT3 [54 ng/dl (87–169 ng/dl)]. Diagnostic gallium 68 - DOTATATE positron emission tomography-computed tomography performed prior to 177Lu-DOTATATE treatment revealed diffuse thyroid uptake. Post-therapy single-photon emission computed tomography also revealed diffuse uptake of 177Lu-DOTATATE in the thyroid gland. Levothyroxine therapy was initiated, and the patient’s symptoms resolved. Summary We report, for the first time, a patient with asymptomatic primary hyperthyroidism who rapidly developed symptomatic primary hypothyroidism 1 month after 177Lu-DOTATATE therapy, accompanied by marked changes in TFTs and thyroid auto-antibody titers, with functional imaging evidence of diffuse uptake of 177Lu-DOTATATE in the thyroid gland. Conclusions Thyroid dysfunction can be associated with PRRT. Thyroid uptake patterns on pre-treatment diagnostic somatostatin analog scans might predict individual susceptibility to PRRT-associated TFT disruption. Therefore, periodic evaluation of TFTs should be considered in patients receiving PRRT.